2019
DOI: 10.3390/w11122434
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Isotopes Associated with the Duration and Distance of Moisture Trajectory in a Westerly-Dominant Setting

Abstract: A Lagrangian diagnostic adjusted using specific humidity, with 6 h intervals along the trajectory and with lifting condensation level as cloud base height, was employed to identify the moisture source regions around the Tianshan Mountains, northwest China. Then, the relationship between precipitation stable isotopes and diagnosed duration–distance of moisture trajectory was analyzed. In this region, the median value of transport duration from moisture source to precipitation sampling site is approximately 3 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The average annual temperature remains below 0 • C, while the precipitation amount range from 115 to 440 mm, primarily concentrated from May to October. The Tianshan (TS) region stands as a "wet island" within the arid and semi-arid northwest China, receiving an average annual rainfall of over 400 mm due to westerly winds transporting moisture along the east-west Oriental mountain range [52,62]. The Muztagh (MZTG) site in the Pamir region of the northwestern TP and Qilianshan station (QLS) in the northeastern TP endure westerly winds throughout the year, featuring a cold climate with average wind speeds surpassing 4.5 m/s, however, MZTG experiences lower precipitation and relative humidity compared to Qilianshan (refer to Supplementary Materials Table S1) [51,63,64].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The average annual temperature remains below 0 • C, while the precipitation amount range from 115 to 440 mm, primarily concentrated from May to October. The Tianshan (TS) region stands as a "wet island" within the arid and semi-arid northwest China, receiving an average annual rainfall of over 400 mm due to westerly winds transporting moisture along the east-west Oriental mountain range [52,62]. The Muztagh (MZTG) site in the Pamir region of the northwestern TP and Qilianshan station (QLS) in the northeastern TP endure westerly winds throughout the year, featuring a cold climate with average wind speeds surpassing 4.5 m/s, however, MZTG experiences lower precipitation and relative humidity compared to Qilianshan (refer to Supplementary Materials Table S1) [51,63,64].…”
Section: Study Areamentioning
confidence: 99%
“…Research on the influence of moisture sources on precipitation isotopes in the TP areas has predominantly concentrated on the southern TP [35,48,49] and the northeastern and western TP [19,50]. However, there is also interest in the far north, such as the Tianshan Mountains [2,[51][52][53], with relatively few investigations on moisture sources in the north of the TP, where sub-cloud evaporation and continental recycling processes hold significance. Consequently, it is imperative to elucidate the impact of moisture sources, transport processes, and local environmental factors on precipitation to understand the mechanism governing regional precipitation isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [29] showed a case study linking the isotopic variation to moisture sources, and found that there is a dominant effect of westerly moisture in summer and of a combined influence of westerly and polar air masses in winter. Wang et al [30,31] demonstrated that the rainfall in westerly-dominated northwest China is related to locally recycled moisture and the advected moisture via Europe and central Asia.…”
Section: Introductionmentioning
confidence: 99%